Scale-up of zinc-air battery electrodes enhanced by 3D X-ray imaging - Benedetto Bozzini; Alessandro Alleva; Elisa Emanuele; Sheraz Gul; Tianzhu Qin; Wenbing Yun; Lucia Mancini (e-Journal of Nondestructive Testing)
The scale-up of successful laboratory-scale zinc-air battery (ZAB) components is a stumbling block towards commercialization of this sustainable, cheap and safe technology. In this work, we consider electrode nanofabrication solutions that have been proved capable of overcoming durability criticalities at laboratory scale, but can miss their goal upon increasing electrode dimensions, owing to hard-to-discern electrode architecture issues. This contribution shows how X-ray computed microtomography can drive R&D of battery components.